Quantifying deformation processes near grain boundaries in α titanium using nanoindentation and crystal plasticity modeling. (November 2016) - Su, Y.; Zambaldi, C.; Mercier, D.; Eisenlohr, P.; Bieler, T.R.; Crimp, M.A.
Abstract: The influence of grain boundaries on plastic deformation was studied by carrying out nanoindentation near grain boundaries (GBs). Surface topographies of indentations near grain boundaries were characterized using atomic force microscopy (AFM) and compared to corresponding single crystal indent topographies collected from indentations in grain interiors. Comparison of the single crystal indents to indents adjacent to low-angle boundaries shows that these boundaries have limited effect on the size and shape of the indent topography. Higher angle boundaries result in a decrease in the pile-up topography observed in the receiving grain, and in some cases increases in the topographic height in the indented grain, indicating deformation transfer across these boundaries is more difficult. A crystal plasticity finite element (CPFE) model of the indentation geometry was built to simulate both the single crystal and the near grain boundary indentation (bi-crystal indentation) deformation process. The accuracy of the model is evaluated by comparing the point-wise volumetric differences between simulated and experimentally measured topographies. Good agreement, in both single and bi-crystal cases, suggests that the crystal plasticity kinematics plays a dominant role in single crystal indentation deformation, and is also essential to bi-crystal indentation. Despite the good agreement, some differences between experimental and simulated topographies were observed. These discrepancies have been rationalized in terms of reverse plasticity and the inability of the model to capture the full resistance of the boundary to slip. This is discussed in terms of dislocation nucleation versus glide in the model and in the physics of the slip transfer process. Highlights: Topography formed in nanoindentation as a measure for plastic deformation. AFM measured single and bi-crystal indent topographies have high reproducibility. Resistance of multiple grain boundaries to plastic flow are quantified. CPFE simulated single and bi-crystal nanoindentation. Quantitative comparison of AFM measured and simulated indentations.